Reinventing the wheel?: Imagining collaborative spaces at the intersection of masculinity studies and feminist studies in biblical scholarship - Larsson, Mikael (Advances in ancient Biblical and Near Eastern research, 2021)
This article examines whether masculinity studies carry on the feminist legacy in biblical scholarship. The investigation proceeds through close readings of a selection of works that, in different ways, highlight the interactions between masculinity studies and feminist studies. To begin with, I trace the development of masculinity studies in three major anthologies on masculinity in biblical traditions (Ovidiu Creangă 2010, 2019, Creangă and Peter-Ben Smit 2014). The focus here lies on masculinity scholars’ explicit positioning in relation to feminist studies, through connection or disengagement, set against actual dialogue with feminist biblical scholarship. Secondly, I address Deryn Guest’s queer critique of masculinity studies in Beyond Feminist Biblical Studies (2012), along with her proposed theoretical platform, "genderqueer criticism". Thirdly, I consider two examples from the other side of the table, namely feminists exploring masculinity, through the works of Claudia Camp (2013) and Rhiannon Graybill (2016). Finally, I conclude with a discussion of the challenges in the field and make some suggestions to facilitate cooperation in the future.